Genotypic diversity and antimicrobial resistance determinants in Salmonella Typhi isolated from children living in informal settlements in Nairobi, Kenya - Miss Susan Kavai; Dr Cecilia Mbae; Dr Sylvia Omulo; Prof Julius Oyugi; Prof Samuel Kariuki (International Journal of Infectious Diseases)
Introduction: Whole genome sequencing (WGS) is an important tool for disease diagnostics and identification of circulating multi-drug resistant (MDR) genotypes of enteric pathogens globally. In typhoid-endemic regions, WGS of Salmonella Typhi (S. Typhi) has identified haplotype 58 (H58) as one of the dominant MDR haplogroups. This case-control study reports on antimicrobial resistance (AMR) genes and genotypic diversity of S. Typhi from sick and asymptomatic children in Mukuru and Kibera informal settlements in Nairobi County. Methods: From 2013 to 2018, children ≤ 16 years presenting to 4 health facilities in Nairobi County were recruited if they had a fever; ≥380C with or without diarrhea. Asymptomatic individuals (controls) who reported to the facilities for vaccinations and with non-typhoid-related symptoms were also recruited. Both groups provided stool samples that were subjected to culture and antimicrobial susceptibility testing for phenotypic analysis of AMR. S. Typhi isolates that showed resistance to ampicillin, co-trimoxazole, and chloramphenicol were considered as MDR and subjected to WGS. Deoxyribonucleic acid (DNA) of 90 S. Typhi isolates (44 from sick and 46 from asymptomatic individuals) was extracted for WGS. Sequencing was done using the Illumina Nextseq2000 platform. The generated raw reads were de novo assembled and pathogen-watch was used for analysis. Results: Of the sequenced isolates, 60(69%) were confirmed to be S. Typhi. All of the S. Typhi belonged to the sequence Type 1 and genotype 4.3.1 (Haplotype 58). Out of the 60 S. Typhi strains 40(67%) were found to have plasmids, out of which 38(95%) had the IncHI1A/IncHI1B (R27) plasmids. The distribution of S. Typhi in sick and asymptomatic individuals was almost equal at 31(51%) and 30(49%). The 60 S. Typhi isolates were observed to have AMR determinants of 6 antibiotics with ampicillin (bla TEM-1D) as the most common, observed in 59 (98%) of the isolates. Point mutations conferring reduced susceptibility to quinolones were detected in 42 (70%) of S. Typhi isolates, 14(33%) gyrA_S83Y, and 28/42 (67%) gyrB_S464F. Discussion: This study reports all MDR S. Typhi sequenced to belong to sequence Type 1. Genotype 4.3.1 (H58) was observed as the most dominant S. Typhi genotype among the symptomatic and asymptomatic individuals. Haplotype 58 is responsible for the spread of MDR phenotypes that carry on IncHI1 plasmids. Conclusion: Circulation of H58 S. Typhi genotypes in Mukuru and Kibera informal settlements especially among asymptomatic individuals reiterates the need for mass vaccination as a control and prevention measure of Typhoid fever in urban informal settlements in Kenya.